Discovery of the genus Neotrichoporoides Girault, 1913 (Hymenoptera: Eulophidae) in Iraq, with three new records - Zainab F. Mansowr; Majid Jafarlu; Hossein Lotfalizadeh (Journal of Insect Biodiversity and Systematics)
Through a survey that was conducted in Basrah Province, Southern Iraq in 2021, specimens were collected from alfalfa fields (Medicago sativa L.) using a sweep net. These specimens were identified as Neotrichoporoides Girault, 1913 (Hymenoptera: Chalcidoidea, Eulophidae), which is a new report of the genus in Iraq. Three species were collected and identified, i.e. Neotrichoporoides basiﬂavus Li & Li, 2021; N. cavigena Graham, 1987; and N. viridimaculatus (Fullaway, 1955). An illustrated key for identifying Neotrichoporoides species in Iraq and notes on diagnostic characters of the newly recorded species along with illustrations are provided. The distribution map of the Iraqi species is presented. Furthermore, a preliminary checklist of recorded species of Eulophidae from Iraq is provided.